Research Status of High Temperature Mine Cooling Technology at Home and Abroad - Li, Xiangwei (International Journal of Natural Resources and Environmental Studies, 2025)
With the gradual mining of the mine to the deep, the mine will face the problem of heat damage, and the high temperature of the working face will seriously affect the production efficiency of the mine. Therefore, it is necessary to adopt the corresponding cooling measures to cool the high temperature mine. This paper aims to summarize the current high temperature mine cooling technology at home and abroad, analyze its advantages and disadvantages, and provide corresponding technical application ideas for high temperature mine cooling.